# Answer to Question #16135 in Linear Algebra for noor

Question #16135

solve the following system or show that it has no solutions

x+2y=7

-2x+y=1

x-y=-2

3x+y=6

x+2y=7

-2x+y=1

x-y=-2

3x+y=6

Expert's answer

Solution. Start with the first, x = -2y + 7, so from the second equation one gets 4y - 14 + y = 1 or y = 3 and, hence x = 1.To conclude, the solution is

(1; 3).

Proceed with the second, x = -2+y, the second equation implies -6+3y+y = 6,

thus y = 3 and x = 1. The solution is (1; 3).

Solution. (1; 3), (1; 3)

(1; 3).

Proceed with the second, x = -2+y, the second equation implies -6+3y+y = 6,

thus y = 3 and x = 1. The solution is (1; 3).

Solution. (1; 3), (1; 3)

## Comments

## Leave a comment